Pragmatic-discursive analysis of letters exchanged between Epifânio Dória and José Calasans (Filologia e Linguística Portuguesa, 2020)
This article aims to present a study on the nature of the epistolary communication between Epifânio Dória and José Calasans, two intellectuals from Sergipe who maintained correspondence for sixteen years. The epistolary corpora under analysis are semi-diplomatic editions, that is, conservative of the state of the language in which the texts were written, of handwritten and typewritten missives by Epifânio Dória (1884-1976) and José Calasans (1915-2001), found in the found in the file of these intellectuals safeguarded at the Historical and Geographic Institute of Sergipe (IHGSE). The textual analysis undertaken, from a philological perspective, considers the examination of the conditions of production and circulation of epistolary texts and their role in history and society. The choice of the letter as an object of research, aiming at reflecting on its contextuality, allowed the philological moment of textual analysis to be combined with a pragmatic perspective, due to the nature of this communicative situation. Thus, in the context of the textual surface, at the pragmatic-discursive level, the verbal routines of opening, pre-closing and closing the letters were systematized and analyzed, according to the model of Interactional Analysis of Epistolary Communication (AICE), proposed by professor and researcher Isabel Roboredo Seara.